2017
DOI: 10.1039/c6cc08006e
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of aligned atomically precise chevron graphene nanoribbons on Cu(111)

Abstract: Atomically precise chevron graphene nanoribbons (GNRs) have been synthesized on Cu(111) substrates by the surface-assisted coupling of 6,11-dibromo-1,2,3,4-tetraphenyltriphenylene (CBrH) and thermal cyclodehydrogenation of the resulting polymer. The GNRs form on Cu(111) epitaxially along the 〈112〉 crystallographic directions, which was found to be in agreement with the computational results, and at lower temperatures than on Au(111). This work demonstrates that the substrate plays an important role in the on-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 19 publications
2
49
0
Order By: Relevance
“…Then, the structure was further confirmed by Schulz et al As another significant feature, GNRs with aligned properties are also attractive for electronic applications. Teeter et al found the resulted chevron GNRs with preferential angle distribution on Cu(111) substrates (Figure l) . Epitaxial effect may have an impact on this aligned phenomenon evidenced by density functional theory (DFT) result.…”
Section: Crucial Elements and Growth Procedures Of Gnrsmentioning
confidence: 94%
See 1 more Smart Citation
“…Then, the structure was further confirmed by Schulz et al As another significant feature, GNRs with aligned properties are also attractive for electronic applications. Teeter et al found the resulted chevron GNRs with preferential angle distribution on Cu(111) substrates (Figure l) . Epitaxial effect may have an impact on this aligned phenomenon evidenced by density functional theory (DFT) result.…”
Section: Crucial Elements and Growth Procedures Of Gnrsmentioning
confidence: 94%
“…l) STM image of GNRs with epitaxial arrangement on Cu(111). Reproduced with permission . Copyright 2017, Royal Society of Chemistry.…”
Section: Crucial Elements and Growth Procedures Of Gnrsmentioning
confidence: 99%
“…[83] 13-AGNR had asmaller band gap than 7-AGNR in the STS spectrum, [82] thus suggesting that increasing the width of the nanoribbon could result in electrical properties more similar to 2D graphene.N ano-structures with zigzag edges are expected to exhibit spin-polarized electronic edge states.H owever, the formation of GNRs with zigzag edges is almost impossible in solution-mediated reactions because of their relatively unstable nature.R emarkably,t he Fasel group reported the first synthesis of full zigzag-edged GNRs (ZGNRs) using U-shaped monomers under UHV conditions. [84] As aconsequence of the strong chemical reactivity at the nanoribbon edges,t his 6-ZGNR was found to be strongly bound to the underlying Au(111) surface,which limits its application under ambient conditions.T he edge passivation approaches could be used to reduce the chemical reactivity and at the same time preserve the electronic properties of the pristine GNRs.S ome hybrid-edge structures have been obtained with appropriately designed precursors, such as chevron-types, [85] chiraltypes, [86] and acene-types. [87] Recently,n ew type zigzag edgeextended GNRs with aw idth of 9 to 11 carbon atoms was derived from zigzag edge-encased poly-(para-2,9-dibenzo[bc,kl]coronenylene) polymer chains.T hese GNRs exhibited ah igh ratio of zigzag (67 %) to armchair (25 %) edge segments.…”
Section: Molecular Reactions:f Ormation Of Chemical Bondsmentioning
confidence: 99%
“…Different metal substrates can affect the surface reaction via interaction with molecules, resulting in varied reaction activities. For example, it is reported that in the synthesis of chevron‐like graphene nanoribbons from 6,11‐dibromo‐1,2,3,4‐tetraphenyltriphenylene, the cyclodehydrogenation temperature on Au(111) (250–440 °C) is much higher than that on Cu(111) (140–200 °C) . Meanwhile, the chevron graphene ribbons produced on Cu(111) prefer to align along the <112> directions, which is absent on Au(111).…”
Section: Controlling Surface Reaction Via Surface Manipulationmentioning
confidence: 99%
“…Aided by the substrate that acts as the catalyst or template in surface reaction, it becomes feasible to prepare target organic networks from precursors with appropriate functional groups. For instance, many complex covalent‐bonded organic nanostructures like nanographenes, graphene nanoribbons, graphdiyne nanostructures, graphdiyne wires, metalated carbyne chains, and the like can be prepared with carefully designed precursors.…”
Section: Controlling Surface Reaction Via Molecular Manipulationmentioning
confidence: 99%